2007
DOI: 10.1038/sj.cdd.4402168
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-based dual molecular targeting by INNO-406, a second-generation Bcr-Abl inhibitor, and ABT-737, an inhibitor of antiapoptotic Bcl-2 proteins, against Bcr-Abl-positive leukemia

Abstract: Bcr-Abl is the cause of Philadelphia-positive (Ph þ ) leukemias and also constitutes their principal therapeutic target, as exemplified by dramatic effects of imatinib mesylate. However, mono-targeting of Bcr-Abl does not always achieve complete leukemia eradication, and additional strategies those enable complete elimination of leukemic cells are desired to develop. Here we demonstrate that INNO-406, a much more active Bcr-Abl tyrosine kinase inhibitor than imatinib, augments the activities of several proapop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 41 publications
1
38
1
2
Order By: Relevance
“…Bim, a proapoptotic Bcl-2 homology 3-only protein (36), is elevated after ablation of Bcr-Abl and epidermal growth factor receptor signaling (37)(38)(39). However, our data showed that the levels of Bim were unperturbed after HHT treatment (Figs.…”
Section: Hht Induces Apoptosis In D816v Kit-expressing Cells and Decrcontrasting
confidence: 54%
“…Bim, a proapoptotic Bcl-2 homology 3-only protein (36), is elevated after ablation of Bcr-Abl and epidermal growth factor receptor signaling (37)(38)(39). However, our data showed that the levels of Bim were unperturbed after HHT treatment (Figs.…”
Section: Hht Induces Apoptosis In D816v Kit-expressing Cells and Decrcontrasting
confidence: 54%
“…As previously reported, INNO-406 shuts down Bcr-Abl and upregulates several BH3-only proteins, such as Bim, Bad, Bmf and Bik, 32 followed by MOMP, which is known as 'the point of no-return' for cell death commitment. 10,33 As INNO-406 inhibits Bcr-Abl signaling as imatinib does, these events probably occur through shutdown of the downstream of Bcr-Abl signaling pathway, signal transducer and activator of transcription and phosphoinositide-3-kinase (PI3K)/Akt pathways.…”
Section: Discussionmentioning
confidence: 71%
“…IM induces apoptosis through the activation of Bim and Bad, BH3-only proteins (1,2). In this context, Bim inhibits all antiapoptotic Bcl-2 proteins, that is, Bcl-2, Bcl-X L and Mcl-1, whereas Bad inhibits only Bcl-2 and Bcl-X L , but not Mcl-1 (20,21,32).…”
Section: Discussionmentioning
confidence: 99%
“…The constitutive active fusion tyrosine kinase (TK) Bcr-Abl is responsible for deregulated cell proliferation and resistance to cytotoxic insults in chronic myelogenous leukemia (CML) cells, whereas the blockade of the BcrAbl signaling pathway by TK inhibitors (TKI) leads to the inhibition of cell proliferation and induces apoptosis mediated by Bim, a proapoptotic BH3-only protein, in CML cells (1)(2)(3). TKIs against Bcr-Abl such as imatinib mesylate (IM) have greatly improved the therapeutic outcome of CML patients, but treatment failure by resistance or intolerance to IM may occur in ∼40% of patients with CML in the chronic phase (4), and even the more potent second generation Bcr-Abl TKIs, such as nilotinib and dasatinib, are not always promising for IM-refractory CML (5,6).…”
Section: Introductionmentioning
confidence: 99%